Antibiofilm Activities in Skin Secretions of Malaysian Frogs - Abdul-Aziz, A; S Razali, M; M S Wan Azmi, W; A Rahman, Z; F F Abdullah, M (International Journal of Engineering and Technology, 2019)
Biofilms are extracellular structures formed by many species of bacteria that attached on various surfaces. The formation of biofilms is responsible for many health problems as they are very difficult to treat effectively due to enhanced resistant to antibiotics. Frog skin secretions contain bioactive compounds that may exhibit antibiofilms properties against biofilms infection. This study aims to screen the presence of antibiofilm activities from lyophilized skin secretions collected from Malaysian frogs. In this study, lyophilized skin secretions from four species of Malaysian frogs were tested for biofilm inhibition activities against the bacteria Staphylococcus epidermidis, ATCC 35984. Antibiofilm activity was tested at three different stages of biofilm formation which were biofilm maturation, biofilm attachment and biofilm dispersion. Biofilm treated with skin secretion from Fejervarya multistriata showed the presence of antibiofilm activities of 45 % which was able to reduce biofilm formation to 55 % at the attachment stage. Similarly, the biofilm formation at the maturation stage was reduced to 65.8 % only. No antibiofilm activities of Fejervarya multistriata was detected at the dispersion stage. The sample showing positive results was fractionated using column chromatography and further purified by C18 reverse phase high-performance liquid chromatography column (HPLC). Mass spectroscopy revealed the presence of a single peptide. In conclusion, frog skin secretion of F. multistriata contains peptide that inhibits biofilm at both attachment and maturation stages.Â